Energizing green cities in Southeast Asia : applying sustainable urban energy and emissions planning - Ostojic, Dejan (Directions in development (Washington, D.C.). Environment and sustainable development., 2013)
"Presents a blueprint for transforming East Asian cities to global engines of green growth by choosing energy efficient solutions for their infrastructure needs, with case studies in Cebu City (the Philippines), Da Nang (Vietnam), and Surabaya (Indonesia) illustrating the use of sustainable urban energy and emissions planning (SUEEP)"--